Plantinga’s epistemology of religion – some questions - Oliveira, Rogel Esteves de (Veritas (Porto Alegre), 2012)
This paper raises some questions and objections to Alvin Plantinga’s epistemology of religion. In Part I, we have a non-believer speaking (an agnostic about God, spirits or the like). She is in fact an epistemologist and is not very comfortable with Plantinga’s reformed epistemology. In Part II, we have a Christian believer, and the questions will therefore be from the perspective of someone who is inside, who sincerely believes the main teachings of Christian religion. We do not mean by those questions, however, that Plantinga’s approach is wrong. It only needs some clarifications.